Quantitative morphometric analysis of the myenteric nervous plexus ganglion structures along the human digestive tract - Mandić, Predrag D; Filipović, Tatjana; Gašić, Miloš; Djukić-Macut, Nataša; Filipović, Milan; Bogosavljević, Ivan (Vojnosanitetski pregled, 2017)
Background/Aim. All the functions of the digestive system are controlled, guided and initiated by the autonomic nervous system. A special part of this system placed in the wall of the gastrointestinal tract is known as the enteric or metasympathetic nervous system. The aim of this study was to analyse myenteric nervous plexus in different parts of the digestive tract. Methods. We examined the myenteric nervous plexus of the esophagus, stomach, duodenum, jejunum, ileum, transverse colon and rectum in tissue samples taken from 30 cadavers of persons aged 20–84 years. After standard histological processing sections were stained with hematoxylin-eosin, cresyl violet (CV) and AgNO3 method. Multipurpose test system M42 was used in morphometric analysis. The results were analyzed by t-test and analysis of variance. Results. The number of neurons per cm2 surface was the lowest in the esophagus (2.045 ± 310.30) and the largest in the duodenum (65,511 ± 5,639). The statistical processing showed significant differences (p < 0.001) in the number of neurons between the esophagus and all other parts of the digestive tract. The maximal value of the average surface of the myenteric nervous plexus neurons was observed in the esophagus (588.93 ± 30.45 μm2) and the lowest in the stomach (296.46 ± 22.53 μm2). Conclusion. There are differences in the number of ganglion cells among different parts of the human digestive tract. The differences range from a few to several tens of thousands of neuron/cm2. The myenteric nervous plexus of the esophagus was characterized by a significantly smaller number of neurons but their bodies and nuclei are significantly larger compared to other parts of the digestive tract.
Keywords: digestive system; myenteric plexus; neurons; cell count; histological techniques; cadaver